Pelatihan Penguatan Literasi dan Numerasi dalam Pemulihan Pembelajaran pada SMP di Kabupaten Ogan Ilir - Suratmi, Suratmi; Ilhami, Akmillah; Azka, Dea Alvionita; Defliyanto, Defliyanto; Nopriyanti, Nopriyanti; Nurhasan, Nurhasan (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to strengthen literacy and numeracy competencies in junior high schools (SMP) in Ogan Ilir Regency that receive low evaluation scores in their educational units. The community service partners consist of 11 junior high schools, represented by the Principals and one Vice Principal in charge of curriculum. The implementation method includes three main stages: 1) Training, 2) Mentoring, and 3) Supervision. The evaluation instruments used include questionnaires, observation sheets, and analysis of participants’ work documents to measure improvements in knowledge, skills, and attitudes related to literacy and numeracy. Data analysis techniques involve descriptive quantitative and qualitative approaches. The results of this community service activity indicate that partner schools have shown increased knowledge and experience in enhancing professional literacy and numeracy competencies, as well as skills in developing literacy- and numeracy-based learning tools relevant to junior high school students.